Determination of Plutonium in Seawater Using Co-Precipitation and Inductively Coupled Plasma Mass Spectrometry With Ultrasonic Nebulisation - Eroğlu, Ahmet Emin; Eroğlu, Ahmet Emin; McLeod, Cameron W.; Leonard, Kinson S.; McCubbin, David (Elsevier Ltd., 1998)
A flow injection–inductively coupled plasma–mass spectrometric (FI–ICP–MS) procedure, utilising ultrasonic nebulisation with membrane desolvation (USN/MD), has been developed for the determination of plutonium (Pu) in seawater at fg l−1 concentration levels. Seawater samples (1 l), after filtration, were subjected to co-precipitation with NdF3, followed by ion exchange to enrich Pu and to reject seawater matrix ions and co-existing uranium. The seawater concentrate (1.0 ml) was then analysed by FI–ICP–MS. The limit of detection for in seawater based on an enrichment factor of 1000 was 5 fg l−1, and precision at the 0.80 pg l−1 level was 12% RSD. Accuracy was verified via recovery experiments, and by comparing survey data for the Irish Sea with that derived by standard methodology based on co-precipitation and α-spectrometry. Concentrations for dissolved in the Irish Sea were in the range of 0.267–0.941 pg l−1 (0.614–2.164 mBq l−1) and 0.051–0.196 pg l−1 (0.428–1.646 mBq l−1), respectively.
Keywords: Plutonium; Seawater; Inductively coupled plasma–mass spectrometry (ICP–MS); Flow injection; Ultrasonic nebulisation